Improving The Beginning Reading Ability of Elementary School Students with Flip Book Media Using The Syllable Method - Rahmawati, Melly; Subiyantoro, Singgih; Purwitasari, Kartika (MANDAILING GLOBAL EDUKASIA, 2025)
The problem of low reading ability of first grade students at SD Negeri 2 Mojoharjo, Sukoharjo Regency, is an important concern that needs to be addressed. The lack of students' ability to recognize letters, compose words, and understand simple texts hinders their mastery of basic literacy. This study aims to improve students' initial reading skills by using flip book media with the syllable method. The research approach, namely Classroom Action Research from Kemmis & Taggart, was applied in two cycles, involving 5 grade 1 elementary school students as subjects. Data were collected through observation, interviews and reading tests, then analyzed descriptively quantitatively to see the improvement in students' early reading skills. The results of the study showed that the flip book media with the syllable method was able to provide a significant increase in reading ability after two learning cycles. This study also emphasized the importance of teacher skills in developing creativity in implementing this media. Overall, these findings add insight into the effectiveness of flip book media using the syllable method in early reading learning and can be a reference for educators and policy makers.